STUDI LITERATUR TENTANG PENGETAHUAN REMAJA TENTANG PENANGANAN DISMENOREA PRIMER - Asriningtias, Winahyu Winahyu; Sendra, Eny; Kristianti, Shinta (Poltekkes Kemenkes Malang, 2022)
The incidence of dysmenorrhea itself according to the World Health Organization is quite high throughout the world. On average in European countries, dysmenorrhea occurs in about 45 until 97Percent of women. With the lowest prevalence in Bulgaria 8.8Percent and the highest reaching 94Percent in Finland. In Indonesia, the figure is estimated at 55Percent of productive women whose activities are disrupted by dysmenorrhea. This type of research is Literature Review using databases including Google Schoolar, ScienceDirect, GARUDA and Research Gate. This article search used the PEOS formula. There are research results showing that respondents have a good level of knowledge, sufficient and less. Respondents handled dysmenorrhea by consuming anchovies painkillers, compressing warm water, eating nutritious foods, exercising lightly and reducing caffeine consumption.